The impact of digital trends on marketing - Daliborka Blazheska; Natasha Ristovska; Sashko Gramatnikovski (UTMS Journal of Economics, 2020)
The growing presence of the internet in people's daily lives gives us the right to think about the growing use of digital marketing. Companies should use the internet and social networks to promote and sell their products, as digital marketing is extremely important for running a business. New developments in global marketing inspire new ways where companies connect with their customers, by focusing on mass marketing. With the help of modern internet, marketing companies carefully choose their clients and build long-lasting relationships with already selected clients. This labor puts an accent on the research of how much Macedonian companies are aware of the impact of digital marketing on business and changes in traditional ways of communication. From the research we can see that it is a necessity to create and apply digital strategies for more efficient communication with the customers, and hence better results in business. Every company should devise a strategy that will combine traditional and modern communication media.
Keywords: M30; M13; 330; digital marketing; social networks; digital strategies; communication; business success